DINAMIKA INSTITUSIONAL DAN POLITIK DATA DALAM PENYALURAN BANTUAN TUNAI PADA MASA KRISIS: ANALISIS INSTITUTIONAL POLITICAL ECONOMY STUDI KASUS LOKAL DI INDONESIA - Ahmad Yusroni; Romy Hermawan (JianE (Jurnal Ilmu Administrasi Negara), 2026)
Cash transfers during crises have become a central instrument of social protection, yet their effectiveness depends heavily on inter-institutional coordination, the timeliness of beneficiary data, and implementation practices at the local level. This study addresses two questions: how institutional coordination, beneficiary data governance, and subnational mediation shape targeting accuracy; and why emergency transfers that alleviate short-term hardship still generate inclusion errors, exclusion errors, and legitimacy-related grievances. The study employs a qualitative case study design through the lens of institutional political economy, drawing on semi-structured interviews with implementing actors, beneficiaries, and local observers, complemented by field observation, document analysis, and contextual administrative statistics. The findings show that uneven coordination capacity among implementing actors and outdated beneficiary registries intensify targeting errors and weaken program legitimacy. Although cash assistance helps sustain household consumption and meet basic needs during crises, its effects remain primarily short-term and protective rather than transformative. This study argues that the effectiveness of cash transfers is shaped not only by the size of the benefit, but also by the interaction between institutional capacity, data quality, and the politics of implementation.